2022
DOI: 10.1093/bjs/znac308.147
|View full text |Cite
|
Sign up to set email alerts
|

P-048 Does Bilateral Repair Increase Complication Rates Compared to Unilateral Repair in Patients Undergoing Laparoscopic Totally Extraperitoneal Inguinal Hernia Surgery?

Abstract: Introduction There is ongoing debate over whether to fix asymptomatic contralateral inguinal hernias during repair of the presenting hernia. This study reviewed the practice of one high-volume hernia surgeon, comparing unilateral and bilateral laparoscopic repairs, to establish if bilateral repair is associated with an increased risk of post-operative complications compared to unilateral repair. Material & Methods All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Complication rates vary between unilateral and bilateral inguinal hernia repairs. A comparative study between the two revealed complication rates of 11.2% for unilateral repairs and 16.5% for bilateral repairs, with no significant difference observed between the groups [ 32 ]. However, another investigation highlighted a higher incidence of postoperative complications within 30 days following bilateral repairs (4.9%) in contrast to unilateral repairs (3.9%), indicating a significantly greater risk associated with bilateral inguinal hernia repair [ 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…Complication rates vary between unilateral and bilateral inguinal hernia repairs. A comparative study between the two revealed complication rates of 11.2% for unilateral repairs and 16.5% for bilateral repairs, with no significant difference observed between the groups [ 32 ]. However, another investigation highlighted a higher incidence of postoperative complications within 30 days following bilateral repairs (4.9%) in contrast to unilateral repairs (3.9%), indicating a significantly greater risk associated with bilateral inguinal hernia repair [ 33 ].…”
Section: Reviewmentioning
confidence: 99%